A fossil anuran from the Lower Cretaceous Sinuiju Formation, North Phyongan Province, Democratic People's Republic of Korea. (December 2022) - So, Kwang-Sik; Jong, Tal-Mi; Won, Chol Guk; Jo, Song-Dae
Abstract: A postcranial skeleton of a Mesozoic frog has been discovered from the third member of the Lower Cretaceous (Barremian-Aptian) Sinuiju Formation, Paektho-dong, Sinuiju City, North Phyongan Province, Democratic People's Republic of Korea (DPRK), which might be referred to Liaobatrachus grabaui Ji and Ji 1998. This frog represents the ﬁrst fossil anuran from the Sinuiju Formation of DPRK and offers us a chance to study and better understand Mesozoic anuran. Highlights: First fossil anuran is reported from the Lower Cretaceous Sinuiju Formation. It was recovered from Paekhto-dong locality near Sinuiju City in DPRK. Sinuiju anuran might be related to the genus Liaobatrachus from NE China.